Maxwell's Equations : Analysis and Numerics - Langer, Ulrich; Pauly, Dirk; Repin, Sergey (Radon series on computational and applied mathematics, 2019)
This volume collects longer articles on the analysis and numerics of Maxwell's equations. The topics include functional analytic and Hilbert space methods, compact embeddings, solution theories and asymptotics, electromagnetostatics, time-harmonic Maxwell's equations, time-dependent Maxwell's equations, eddy current approximations, scattering and radiation problems, inverse problems, finite element methods, boundary element methods, and isogeometric analysis.- Resumé vydavatel